Substance Use Outcomes from Two Formats of a Cognitive-Behavioral Intervention for Aggressive Children: Moderating Roles of Inhibitory Control and Intervention Engagement - Lochman, John E. (Brain Sci, 2021)
Although cognitive-behavioral interventions have reduced the risk of substance use, little is known about moderating factors in children with disruptive behaviors. This study examined whether aggressive preadolescents’ inhibitory control and intervention engagement moderates the effect of group versus individual delivery on their substance use. Following screening for aggression in 4th grade, 360 children were randomly assigned to receive the Coping Power intervention in either group or individual formats. The sample was primarily African American (78%) and male (65%). Assessments were made of children’s self-reported substance use from preintervention through a six-year follow-up after intervention, parent-reported inhibitory control at preintervention, and observed behavioral engagement in the group intervention. Multilevel growth modeling found lower increases in substance use slopes for children with low inhibitory control receiving individual intervention, and for children with higher inhibitory control receiving group intervention. Children with low inhibitory control but who displayed more positive behavioral engagement in the group sessions had slower increases in their substance use than did similar children without positive engagement. Aggressive children’s level of inhibitory control can lead to tailoring of group versus individual delivery of intervention. Children’s positive behavioral engagement in group sessions is a protective factor for children with low inhibitory control.